Do parental leaves make the motherhood wage penalty worse? Assessing two decades of German reforms - Gabriele Mari; Giorgio Cutuli (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Women-friendly policies may have perverse effects on the wages of employed women and mothers in particular. Yet few have addressed the causal impact of such policies and the mechanisms they might trigger at the individual level to produce such wage responses. We assess if and how two decades of reforms of parental leave schemes in Germany have shaped changes in the motherhood wage penalty over time. We compare two sweeps of reforms inspired by opposite principles, one allowing for longer periods out of paid work, the other prompting quicker re-entry in the labour market. We deploy panel data (SOEP 1985-2014) and a within-person difference-in-differences design. Motherhood wage penalties were found to be harsher than previously assessed in the 1990s. As parental leave reform triggered longer time spent on leave coupled with better tenure accumulation, wage losses for mothers remained stable in this first period. Conversely, we can no longer detect motherhood wage penalties for women affected by the later reform. Shorter career breaks and increased work hours may have benefited new mothers in the late 2000s, leading to a substantial improvement in their wage prospects.
Keywords: D13; J13; J16; J31; 330; parental leave; motherhood wage penalty; difference-in-difference; gender inequality